Functional niche differences between native and invasive tree species from the southern Brazilian mixed forest - LARSEN,JANAINA G. (2020)
Abstract Biological invasion is a major threat to global biodiversity and ecosystem services. We examined the functional traits similarity between a set of native and non-native invasive tree species from the Southern Brazilian subtropical mixed forest, part of an important global hotspot for biodiversity conservation. We hypothesized that invasive species occupy marginal niche spaces. We ordered the species using the Principal Component Analysis based on their wood density, leaf area, and specific leaf area. These are all important traits that summarize essential ecological strategies associated with resource acquisition and conservation. Functional overlaps between non-native and native species were analyzed through kernel density estimation of continuous traits data. While native and non-native invasive species were distributed along the same functional gradients, the position of non-native species in the functional space is species and traits specific. We concluded that within Brazilian subtropical mixed forests, the functional dissimilarity as a key factor in invasion success could not be generalized for all species and traits.